2009
DOI: 10.1182/blood-2009-01-197871
|View full text |Cite
|
Sign up to set email alerts
|

AML with mutated NPM1 carrying a normal or aberrant karyotype show overlapping biologic, pathologic, immunophenotypic, and prognostic features

Abstract: Acute myeloid leukemia (AML) with mutated NPM1 usually carries normal karyotype (NK), but it may harbor chromosomal aberrations whose significance remains unclear. We addressed this question in 631 AML patients with mutated/ cytoplasmic NPM1. An abnormal karyotype (AK) was present in 93 of 631 cases (14.7%), the most frequent abnormalities being ؉8, ؉4, ؊Y, del(9q), ؉21. Chromosome aberrations in NPM1-mutated AML were similar to, but occurred less frequently than additional chromosome changes found in other AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(107 citation statements)
references
References 50 publications
4
102
1
Order By: Relevance
“…NPM1 mutations are often the only genetic abnormality detected in AML blasts and are very stable during the course of the disease (Meloni et al, 2008), therefore likely representing a reliable marker for monitoring minimal residual disease . Only 15% of NPMc þ AML show a complex karyotype, although in these cases chromosomal alterations are often present only in a portion of AML blasts, suggesting they represent secondary events (Haferlach et al, 2009). Accordingly, no differences have been found in terms of clinical or biological behavior between NPMc þ AML with normal karyotype or those bearing additional chromosomal abnormalities Haferlach et al, 2009).…”
Section: Role Of Npm In Human Hematological Malignanciesmentioning
confidence: 83%
“…NPM1 mutations are often the only genetic abnormality detected in AML blasts and are very stable during the course of the disease (Meloni et al, 2008), therefore likely representing a reliable marker for monitoring minimal residual disease . Only 15% of NPMc þ AML show a complex karyotype, although in these cases chromosomal alterations are often present only in a portion of AML blasts, suggesting they represent secondary events (Haferlach et al, 2009). Accordingly, no differences have been found in terms of clinical or biological behavior between NPMc þ AML with normal karyotype or those bearing additional chromosomal abnormalities Haferlach et al, 2009).…”
Section: Role Of Npm In Human Hematological Malignanciesmentioning
confidence: 83%
“…In a recent study designed to establish the prognostic value of these additional genetic abnormalities, we found that prognosis in AML with mutated NPM1 is not influenced by karyotype. 109 Given its favourable prognosis, it is recommended that NPM1-mutated/FLT3-ITD negative AML be treated by conventional chemotherapy regimens with or without autologous stem cell transplantation. Schlenk et al 108 recently reported that NPM1-mutated AML patients without FLT3-ITD did not appear to benefit from allogeneic stem cell transplantation in first complete remission.…”
Section: Impact Of Mutated Cytoplasmic Nucleophosmin On Clinical Manamentioning
confidence: 99%
“…The frequent co-overexpression of HOXA9 and MEIS1, particularly in leukemias harboring MLLrearrangements [18,19], suggests a vital genetic interaction between the cofactors, which may be required for leukemia maintenance in a context-dependent manner [20][21][22][23]. Notably, expression of HOXA9 and MEIS1 is also associated with cytogenetically normal AML (CN-AML) where no major genetic aberrations have been identified [24]. Direct co-overexpression of HOXA9 and MEIS1 results in an aggressive, transplantable, and tractable myeloid leukemia in mouse models with a cytogenetically normal genetic background [25].…”
Section: Introductionmentioning
confidence: 99%